Web-Based Information System for SME - Hornof, Johan (2011)
Nowadays, every single company needs to operate with large amount of data to support daily operation. Although there is pretty good market offer with information systems for managing various kinds of data, only small part of them is suitable for the company that does not deal with sale of goods but provides services, particularly marketing services or IT services (e.g. programming). This thesis describes the design and development of such a system which has a main goal to satisfy the needs of small to medium companies whose needs are still different than what currently marketed products can offer. Such a system will, apart from other functions, be able to manage projects and track work time of employees.